2018
DOI: 10.1186/s40902-018-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Positional change in mandibular condyle in facial asymmetric patients after orthognathic surgery: cone-beam computed tomography study

Abstract: BackgroundWe evaluated change in the mandibular condyle after orthognathic surgery using cone-beam computed tomography (CBCT) in patients with facial asymmetry.MethodsThirty patients with skeletal class III malocclusion and mandibular prognathism or facial asymmetry were classified into two groups according to the amount of menton deviation (MD) from the facial midline on anteroposterior (AP) cephalogram: group A (asymmetry, MD ≥ 4 mm; n = 15) and group B (symmetry, MD < 4 mm; n = 15). Position and angle of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 22 publications
2
33
1
1
Order By: Relevance
“…The proportions of anteriorly positioned condyles decreased only minimally. This finding is in accordance with the previous research of Kim et al [43,44], Iguchi et al [45], and Choi et al [46,47]. In the maxillary single-jaw surgery group, the condyles were positioned anteriorly or concentrically before the surgery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proportions of anteriorly positioned condyles decreased only minimally. This finding is in accordance with the previous research of Kim et al [43,44], Iguchi et al [45], and Choi et al [46,47]. In the maxillary single-jaw surgery group, the condyles were positioned anteriorly or concentrically before the surgery.…”
Section: Discussionsupporting
confidence: 92%
“…The available evidence regarding angular rotation in the axial plane is controversial. Several studies [46,47,49,50] found that condyles tend to rotate inwards immediately after surgery. However, longer-term follow-ups showed that condyles tend to regress to their original position.…”
Section: Discussionmentioning
confidence: 99%
“…Byung-Joon Choi y cols. 23 , en su estudio, reportan que no se encuentran cambios significativos en la evaluación de la posición condilar. En nuestra experiencia no se encontraron cambios significativos entre la medición condilar inicial y la medición final.…”
Section: Discussionunclassified
“…[ 2 ] One of the most common methods in the management of excessive mandibular prognathism is mandibular setback using bilateral sagittal split ramus osteotomy (BSSRO), which has many advantages including a wide contact area between segments facilitating healing as well as convenient relocation of the distal segment; it also has certain complications including condylar displacement and a rather high rate of relapse. [ 1 2 3 4 5 ] In BSSRO, the mandible is divided into distal and proximal segments to enable their displacement. [ 4 6 ] In such cases, it is of significant value to maintain the initial positions of the condylar heads.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 4 5 ] In BSSRO, the mandible is divided into distal and proximal segments to enable their displacement. [ 4 6 ] In such cases, it is of significant value to maintain the initial positions of the condylar heads. [ 4 6 ] because it can help prevent post-BSSRO relapse.…”
Section: Introductionmentioning
confidence: 99%